Legislation and Judicial Practice on Illegitimate Children in 19th Century Serbia - Kulauzov, Maša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
Legal position of non-marital children according to 19th century Serbian legislature and judicial practice is examined in this paper. Provisions and court decisions on personal rights, property rights and rights of succession of illegitimate children are presented and critically analyzed. Children born out of wedlock were not equal to children born in lawful marriage. Therefore, significance of legalization of illegitimate children regarding improvement of their legal status is accentuated. As non-marital relationships were condemned in patriarchal Serbian 19th century society, illegitimate children were considered a product of sin and family disgrace. Hence, legislative and judicial attemps to protect their interests and improve their legal position are emphasized in this paper. Beside legalization, adoption was also the way to better position of illegitimate children in great extent, as adopted child was granted the status of a child born in lawful marriage. That is a reason why judicial practice concerning adoption, widespread in 19th century Serbia, is scrutinized and critically analyzed in the article.